Reimagining Newsroom Collaboration: How Two European News Nonprofits Are Inviting Citizens In. (27th May 2020) - Konieczna, Magda
ABSTRACT: News nonprofits in the U.S. have been proliferating over 15 years as a way of addressing troubles in the business model for news. For these newsrooms, collaboration, with each other and with mainstream news, has emerged as a key way to build readership and attain relevance in a crowded media space. Still, past research has told us that the strong connection to mainstream news has constrained these organizations' critique of journalism. In Europe, nonprofit news remains nascent and represents a response to declining trust in and engagement with journalism, and rising populism across the continent. Against this very different context, this study examines two players at the forefront of the European news nonprofit movement. It demonstrates the path dependency inherent in the origins of these organizations: In Europe, they are a response to a different societal change, and thus developed rather differently than did their peers in the United States, with a focus on redefining the idea of collaboration and the role of their audiences by seeing citizens as collaborators, both in the creation and in the dissemination of news. By seeing citizens as collaborators, not just readers, they work to empower and build news audiences as well as participants.